The emerging radiographer's transient community service professional career pathway - Bonita B. Johnson; Chandra R. Makanjee; Willem A. Hoffmann (AOSIS, 2019)
Background: Post-qualification regulatory 12-month community service (CS) was implemented in South Africa in 1998. Since the implementation, studies have been conducted in various disciplines to measure the impact on health services and on the affected professionals, but these did not include radiography professionals. Aim: This study explored the expectations and experiences of student radiographers in respect of the CS concept as an integral transitional career pathway from the student radiographer role to that of a provisional practitioner in transit to acquiring registered radiographer practitioner status. Research methods: The research design entailed a qualitative exploratory approach using a longitudinal data collection approach. That is, data collection from the purposefully selected student radiographers' focus group discussions, as well as from placement institutions' qualified professionals and managers, formed the triangulated data sources. In addition, individual interviews were conducted post-placement until data and thematic saturation had been reached. Tesch's (1990) method was used for the data interpretation and analysis. Results: The themes that emerged reflected the preparedness of these students to fulfil the requirements, their experiences of their anticipated placement institution, preparedness for their roles and responsibilities and uncertainties about their readiness for the actual encounter. A golden thread throughout was critical self-reflection on their ability, adaptability and capability to meet the requirements of the system, namely the community placement institutions and appeasing the Department of Health. Conclusion: The study illustrates, by means of a framework, the student radiographers' journey in transit to acquiring eligibility as registered radiography practitioners in a regulated career pathway.